Influence of hydrocolloids on quality characteristics, functionality and microstructure of spinach puree–enriched instant noodles. Issue 6 (21st April 2020) - Shere, P.D.; Sahni, Prashant; Devkatte, A.N.; Pawar, V.N.
Abstract : Purpose: Noodles are good vehicles for the enrichment and can be enriched with vegetable purees. However, this enrichment can alter quality attributes of noodles with resultant effect on its sensorial attributes. The purpose of this paper is to study the effect of addition of different hydrocolloids on the microstructural and quality characteristics of instant noodles enriched with spinach puree. Design/methodology/approach: Preliminary trials were carried out for the standardization level of addition of spinach puree in noodle formulation. Carboxymethyl cellulose (CMC) and guar gum were added in the noodle formulation at 0.25, 0.5 and 0.75 per cent level of incorporation. The effect of addition of hydrocolloids was evaluated on the cooking quality, sensory attributes, texture characteristics and microstructure of the noodles. Findings: The most acceptable ratio for the formulation of the noodles was found to be 40 g spinach puree per 100 g refined wheat flour. Addition of hydrocolloids resulted in the increase in the cooking time, cooking weight, water absorption and swelling index. Significant decrease in the cooking loss was observed with the increase in the level of CMC (from 7.4 to 6.1 per cent) and guar gum (from 7.4 to 7 per cent). Addition of CMC and guar gum up to 0.5 per cent and 0.25 per cent, respectively, improved the texture, overall acceptability and mouthfeel attributing to complimentary interaction between starch, fibre and hydrocolloids observed at microstructural level; however, further increase in the level of incorporation resulted in stickiness and sliminess in the noodle strands. Practical implications: It is found that 0.5 per cent CMC and 0.25 per cent guar gum can be used for the enhancement of quality characteristics of the spinach puree enriched noodles. Originality/value: Intervention of incorporation of hydrocolloids in spinach puree–enriched instant noodles delivers healthy and nutritious product without compromising on its sensorial and quality attributes.